Scada Implementation for Monitoring Power Source Transfer Status in Automatic Transfer Switch (ATS) at The Automation Laboratory, Electrical Engineering Department, Politeknik Negeri Manado - Diana Debora Rondonuwu; Natanael Varenheith Sombounaung; Bastian Jobel Mewengkang; Marson James Budiman; Maksy Sendiang (Journal of Social Research, 2026)
This study addresses the growing need for reliable and uninterrupted electrical power systems in educational automation laboratories, where power disturbances can disrupt experiments, damage sensitive equipment, and reduce operational efficiency. The research aims to design, implement, and evaluate a Supervisory Control and Data Acquisition (SCADA) system for monitoring power source transfer status in an Automatic Transfer Switch (ATS) at the Automation Laboratory of the Electrical Engineering Department, Politeknik Negeri Manado. The study employed an experimental and engineering-based research method involving system design, hardware integration, software programming, and performance testing. The system utilized a Siemens S7-1200 Programmable Logic Controller (PLC), Modbus TCP/IP communication, and WinCC Flexible SCADA software for real-time monitoring and control. Data were collected through functional testing, communication latency measurements, and reliability evaluations over 50 transfer cycles using a 3 kW load simulation. The results showed that the SCADA-ATS system successfully monitored transfer operations with a data update latency below 200 ms and an average transfer switching time of 2.31 seconds, fully complying with IEC 60947-6-1 standards. Furthermore, the system achieved a 100% transfer success rate and accurate voltage and frequency monitoring. In conclusion, the implemented SCADA system effectively improves operational reliability, monitoring transparency, and educational learning quality in laboratory power management systems.